Reconfigurable Radio‐Frequency High‐Electron Mobility Transistors via Ferroelectric‐Based Gallium Nitride Heterostructure. (10th April 2022) - Yang, Jeong Yong; Yeom, Min Jae; Lee, Jaeyong; Lee, Kyusang; Park, Changkun; Heo, Junseok; Yoo, Geonwook
Abstract: The wireless communication and power transmission environment varies widely depending on time and place, and thus reconfigurable devices and circuits are in high demand due to the significant increase in complexity of the power stage and chip size required for current non‐reconfigurable device‐based systems. Reconfigurable radio‐frequency (RF) devices, however, are difficult to demonstrate due to the lack of suitable materials with desirable material properties that can also be integrated with conventional high‐power materials. Here, reconfigurable gallium nitride (GaN) high‐electron mobility transistors (HEMTs) that are heterointegrated with 2D van der Waals‐interfaced α‐In2 Se3 semiconductor are demonstrated. The switchable ferroelectric polarization of the 2D α‐In2 Se3 layer is exploited to control the 2D electron gas charge density in the GaN channel. Further, a native interfacial indium oxide layer between the gate dielectric and α‐In2 Se3 functions as a charge trapping layer, boosting the effect of the ferroelectric α‐In2 Se3 layer. The fabricated HEMTs exhibit the sharpest subthreshold slope with tunable threshold voltage, transconductance, and maximum frequency in the range of several GHz under the application of a fast pulsed gate‐voltage signal without sacrificing the performance. The results clearly demonstrate the immense potential of ferroelectric‐based mixed‐dimensional heterostructures as a viable pathway toward simple and compact reconfigurable RF systems. Abstract : Reconfigurable radio‐frequency (RF) gallium nitride high‐electron mobility transistors (HEMTs) heterointegrated with a two‐dimensional ferroelectric semiconductor are demonstrated. The fabricated HEMTs exhibit the sharpest subthreshold slope with tunable threshold voltage, transconductance, and maximum frequency in the range of several GHz under a fast pulsed gate‐voltage signal. The tunability is exploited to show reconfigurable RF characteristics toward wireless communication and power transmission applications.